Examination of the Origin and Branching Direction of the Anterior Medial Malleolar Artery From the Anterior Tibial Artery: A Cadaveric Study. Issue 2 (April 2019) - Tonogai, Ichiro; Hayashi, Fumio; Tsuruo, Yoshihiro; Sairyo, Koichi
Background . This study characterized the anterior medial malleolar artery (AMMA) branching from the anterior tibial artery (ATA) to identify problems in anterior ankle arthroscopy possibly contributing to injury to the AMMA. Methods . Barium was injected into 12 adult cadaveric feet via the external iliac artery and the origin and branching direction of the AMMA were identified on computed tomography. Results . The AMMA originated from the level of the ankle joint and below and above the ankle joint line (AJL) in 4 (33.3%), 6 (50.0%), and 1 (8.3%) specimen, respectively. Mean distance from the AJL to the branching point of the AMMA on the sagittal plane was 2.5 mm distal to the AJL. Mean angle between the distal longitudinal axis of the ATA and AMMA was 83.2°. Conclusions . This study established the origin and branching of the AMMA from the ATA. The AMMA should be examined carefully during ankle arthroscopy. Levels of Evidence: Level IV: Cadaveric study